Temporal variation in the abundance of two species of thrushes in relation to fruiting phenology in the Atlantic rainforest - de Castro, Everaldo Rodrigo; Côrtes, Marina Corrêa; Navarro, Luis; Galetti, Mauro; Morellato, Leonor Patrícia C. (Emu, 2012)
When fruit resources in tropical forests are scarce, frugivorous birds might track fruiting by expanding their home-ranges or by moving. We tested whether the abundance of the Yellow-legged Thrush (Turdus flavipes) and White-necked Thrush (T. albicollis) is correlated with the fruiting of the dominant palm tree (Juçara Palm, Euterpe edulis) and fruiting within the tree community as a whole in three Atlantic rainforest types (restinga, lowland, and premontane forests) in south-eastern Brazil over 3 years. We monitored abundance of the two species of thrush and their consumption of fruit, and fruiting patterns of Juçara Palms and the tree community as a whole. Juçara Palms accounted for 45 and 28% of the feeding bouts of Yellow-legged Thrush and White-necked Thrush. The abundance of Yellow-legged Thrushes was positively correlated with fruiting of Juçara Palms, but not to fruiting of the tree community, in all forest types. White-necked Thrushes ate a greater diversity of fruits and its abundance was neither correlated with fruiting of Juçara Palms or to fruiting of the tree community. We suggest that fruits of Juçara Palms constitute a paramount food resource for Yellow-legged Thrushes and may influence movement and abundance of the species in different vegetation types and elevations in the Atlantic rainforest, whereas White-necked Thrushes employ other feeding strategies to persist in periods of fruit scarcity.